2023
DOI: 10.3390/molecules28083512
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Phenolic Compounds, Antioxidant and Antibacterial Activities of Extracts from Different Plant Organs of Meadowsweet (Filipendula ulmaria (L.) Maxim.)

Abstract: Meadowsweet (Filipendula ulmaria (L.) Maxim.) has been widely used in the treatment of various diseases. The pharmacological properties of meadowsweet are derived from the presence of phenolic compounds of a diverse structure in sufficiently large quantities. The purpose of this study was to examine the vertical distribution of individual groups of phenolic compounds (total phenolics, flavonoids, hydroxycinnamic acids, catechins, proanthocyanidins, and tannins) and individual phenolic compounds in meadowsweet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
0
12
1
2
Order By: Relevance
“…Different plant parts such as stems, roots, leaves, and flowers, are often collected from the wild or from a cultivated environment. Due to the different distribution or constituency of various bioactive compounds in different parts of the plants [ 178 , 179 , 180 ], a thorough knowledge from literature or indigenous knowledge systems is required to determine the specific plant parts which need to be harvested for the specific application/investigation.…”
Section: Steps For the Discovery Of Antiviral Compounds In Plant Meta...mentioning
confidence: 99%
“…Different plant parts such as stems, roots, leaves, and flowers, are often collected from the wild or from a cultivated environment. Due to the different distribution or constituency of various bioactive compounds in different parts of the plants [ 178 , 179 , 180 ], a thorough knowledge from literature or indigenous knowledge systems is required to determine the specific plant parts which need to be harvested for the specific application/investigation.…”
Section: Steps For the Discovery Of Antiviral Compounds In Plant Meta...mentioning
confidence: 99%
“…Overall, continued interdisciplinary research efforts are necessary to unlock the full therapeutic potential of antimicrobial compounds derived from Caucasian medicinal plants and address the pressing global challenge of antibiotic resistance. gallic acid 0.8 mg/g extract caftaric acid 0.6 mg/g extract chlorogenic acid 1.3 mg/g extract p-coumaric acid 0.2 mg/g extract catechin 4.1 mg/g extract rutin 4.8 mg/g extract isoquercitrin 2.6 mg/g extract ellagic acid 0.4 mg/g extract Gram-positive, Gram-negative [60] Middle stem 60% ethanol extract Simple phenolic compounds (phenolic acids) Polyphenols (flavonoids) gallic acid 1.3 mg/g extract caftaric acid 0.05 mg/g extract chlorogenic acid 0.2 mg/g extract ellagic acid 0.4 mg/g extract isoquercitrin 0.07 mg/g extract Gram-positive, Gram-negative [60] Flowers 60% ethanol extract Simple phenolic compounds (phenolic acids) Polyphenols (flavonoids) gallic acid 5.8 mg/g extract caftaric acid 2.9 mg/g extract chlorogenic acid 0.3 mg/g extract caffeic acid 0.1 mg/g extract p-coumaric acid 0.04 mg/g extract ellagic acid 5.8 mg/g extract rutin 4.2 mg/g extract isoquercitrin 2.4 mg/g extract spiraeoside 20.4 mg/g extract cymaroside 0.09 mg/g extract Gram-positive, Gram-negative [60] Simple phenolic compounds (phenolic acids) 2,3-hexahydroxydiphenoyl-glucose 6.9 mg/g DW sanguiin H-10 derivative 1.9 mg/g DW punicalagin gallate 9.9 mg/g DW sanguiin H-1 8.3 mg/g DW b-type (epi)catechin dimer 6.1 mg/g DW catechin 7.4 mg/g DW quercetin-galloyl-glucoside 2.9 mg/g DW quercetin-glucoside 18.6 mg/g DW kaempferol-glucuronide 7.6 mg/g DW 3-caffeoylquinic acid 1 mg/g DW caffeic acid-glucoside 2.4 mg/g DW chlorogenic acid 1.6 mg/g DW p-coumaroylquinic acid 2.8 mg/g DW Gram-positive, Gram-negative [64]…”
Section: Sulfur-containing Compounds Of Allium Speciesmentioning
confidence: 99%
“…In parallel to this result, aqueous extract of field-grown aerial parts in our study showed strong antibacterial potency againts S. aureus (Table 1). Savina et al [31] evaluated aqueous ethanol extract of various parts of F. ulmaria and observed susceptibility of P. aeruginosa to upper leaves, fruits, and flowers. Similarly, P. aeruginosa showed moderate susceptibility to aqueous and ethanol extract of fieldgrown F. ulmaria aerial parts (Table 1).…”
Section: Antibacterial Assaymentioning
confidence: 99%